Mechanical and Self-Healing Properties of Stone Mastic Asphalt Containing Encapsulated Rejuvenators - Norambuena-Contreras, Jose; Yalcin, Erkut; Hudson-Griffiths, Robin; Garcia, Alvaro (Asce-Amer Soc Civil Engineers, 2019)
This paper presents an experimental study to evaluate the mechanical and crack-healing properties of stone mastic asphalt (SMA) mixtures with encapsulated rejuvenators. With this goal, calcium alginate capsules with encapsulated sunflower oil as the rejuvenating agent have been manufactured and added into the SMA mixtures. Physical and mechanical properties of SMAwith and without capsules have been evaluated following the British standard tests. Healing properties of SMA by the action of capsules have been assessed using three-point bending (3PB) tests applied on test beams conditioned at different healing times, from 5 to 216 h. The spatial distribution of the capsules in the SMA mixtures was evaluated by using X-ray computed microtomography. Results showed that the capsules can resist the manufacturing process without significantly reducing their properties. Additionally, testing of the mechanical properties of SMA mixtures with and without encapsulated rejuvenators presented similar results. Moreover, capsules showed a good spatial distribution inside the SMA samples. It was found that capsules with encapsulated oil increase the crack-healing properties of SMA when compared to mixtures without encapsulated rejuvenators. Overall, the results proved that the capsules with asphalt crack-healing purposes can be safely used in asphalt pavement construction without affecting its properties.
Keywords: Stone mastic asphalt; Rejuvenating agent; Calcium alginate capsules; Capsule influence; Stiffness modulus; Fatigue behavior; Self-healing capability; Capsule distribution